PSYCHOLOGICAL CHARACTERISTICS OF PATIENTS INFLUENCING ON THE COMMITMENT TO IMPLEMENT THE RECOMMENDATIONS OF DENTISTS - E. V. Sitkina; V. V. Tachalov; E. R. Isaeva; L. U. Orechova; T. V. Kudryavtseva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The psychological peculiarities of dental patients with periodontal disease are summarized here. Also, the article presents the description of patients with positive and negative dynamics of treatment.Objective  – to identify relationships between the characteristics of the patient’s personality and their implementation to the recommendations of dentist.Materials  and Methods. 45 people were examined, an average age of 43 years. The following psychodiagnostic methods were used: 1) the multidimensional questionnaire on health; 2) the test «Diagnosis of interpersonal relationships»; 3) characterological questionnaire by K. Leonhard&T. Shmishek; 4) individually-typological questionnaire by Sobchik L.N.; 5) the questionnaire of self-evaluation status;  6) personality Inventory of Bekhterev Institute. These dental indexes of oral health were measured: 1) CPITN; 2) PMA; 3) Saxer & Muhlemann; 4) Silness & Loe; 5) OHI-S.Results.  According to the results of two measurements of dental indexes, 3 groups of patients were identified: 1) with good oral hygiene; 2) with poor hygiene and positive dynamics (improving dental health index); 3) with poor hygiene and negative dynamics (deterioration indexes). The interrelation of the recommendations  of a dentist with the personal characteristics of patients was found.Summary.  Most patients have tried to follow the dentist’s recommendations for oral care, as evidenced by the decline in dental health indexes in the second survey. Differences in personal characteristics of patients, following and not following the recommendations were revealed, also, the gender differences in the groups with improvement and deterioration indexes were found.